Potential Relationship Between Aerosols and Positive Cloud-to-Ground Lightning During the Warm Season in Sichuan, Southwest China - Zhao, Pengguo; Zhang, Yuanyang; Liu, Chang; Zhang, Peiwen; Xiao, Hui; Zhou, Yunjun (Frontiers in Environmental Science, 2022)
This study discussed the influence of aerosols on the relative frequency of positive cloud-to-ground (CG) lightning and its dependence on thermodynamic and cloud-related factors in Sichuan during the warm season from 2005 to 2017. The relative frequency of positive CG lightning is defined as the proportion of positive CG lightning flashes to total CG lightning flashes. Although the total CG lightning density in the Western Sichuan Plateau is significantly lower than that in the Sichuan Basin, the relative frequency of positive CG lightning is higher than that in the basin. Convective available potential energy (CAPE) and vertical wind shear in the low- to mid-level of the troposphere (SHEAR-5km) are the controlling factors of positive CG lightning frequency. A small CAPE and a large SHEAR-5km represent weak convection, which is more conducive to the generation of positive CG lightning. The upper main positive charge region in the thriving thunderstorm is higher from the ground, which is not conducive to the transport of positive charge to the ground, so it is not conducive to the generation of positive CG lightning. In the basin, the relationship between aerosols and positive lightning is not significant, which may be due to the strong total CG lightning and the low proportion of positive CG lightning. In the plateau, both sulfate aerosol and black carbon (BC) aerosol have a significant inhibition effect on positive CG lightning relative frequency. Sulfate aerosol stimulates the ice-phase process through a microphysical effect and promotes the development of convection. The distribution of the main positive charge center is higher, which is not conducive to the transport of positive charge to the ground and the generation of positive CG lightning. The significant heating effect of BC aerosol on the lower troposphere makes the convective development more vigorous and is not conducive to the occurrence of positive CG lightning.